Differences in body composition according to functional ability in preschool-aged children with cerebral palsy - Walker, J.; Bell, K.; Stevenson, R.; Weir, K.; Boyd, Roslyn; Davies, P. (2015)
Background & aims: Altered body composition is evident in school children with cerebral palsy (CP). Fat free mass and fat mass amounts differ according to functional ability and compared to typically developing children (TDC). The extent to which body composition is altered in preschool-aged children with CP is unknown. We aimed to determine the fat free mass index (FFMI) and body fat percentage (BF%) of preschool-aged children with CP and investigate differences according to functional ability and compared to TDC. Methods: Eighty-five children with CP (68% male) of all functional abilities, motor types and distributions and 16 TDC (63% male) aged 1.4–5.1 years participated in this cross-sectional study. Body composition was determined via isotope dilution. Children with CP were classified into groups based on their Gross Motor Function Classification System (GMFCS) level. Statistical analyses were via ANOVA, ANCOVA, post-hoc Tukey HSD tests, independent t-tests and multiple regressions. Results: There were no significant differences in FFMI or BF% when comparing all children with CP to TDC. Children classified as GMFCS levels III, IV and V had significantly lower FFMI levels compared to children classified as GMFCS I and II (p < 0.05). Children of GMFCS IV and V had the highest mean (±SD) BF% of all children (24.6% (±10.7%)), significantly higher than children of GMFCS I and II (18.6% (±6.8%), p < 0.05). Conclusions: Altered body composition is evident in preschool-aged children with CP, with a trend towards lower FFMI levels and greater BF% across functional ability levels from GMFCS I to V. Further research is required to determine optimal body composition parameters and investigate contributing factors.